Hatim tai landon main - A Hameed (Ferozesons; Lahore, 2002)
"Hatim Tai Landon Main" narrates the inspiring journey of Hatim Tai$1 (Bs legendary deeds of kindness and bravery, set against the backdrop of his impact and influence beyond his homeland, illustrating the universal values of generosity and honor.s